Identity formation in the novel : orientalism, modernity and Orhan Pamuk - Dollar, Cathlene Elizabeth (Department of Religious Studies, 2015)
The novelist Orhan Pamuk rose to prominence as a writer in the midst of the westernized, secular Turkish community in the late twentieth century. Pamuk has insisted that he has attempted to depart from the overtly political style of other writers in his generation. Instead, he strives for his work to appear more poetic and personal. Pamuk's fiction is widely categorized by his experimental, sometimes postmodernist literary techniques. Pamuk's style is a stark departure from the more typical socio-political motifs that have characterized much of contemporary Turkish literature. Edward Said' s critique in Oriental ism and his later theory that the relationship between culture and empire is depicted in the novel in Culture and Imperialism forms one portion of the theoretical model which is used in this dissertation to analyze Pamuk's literature. Said's theory is appropriate because Pamuk's search for identity is strongly characterized by concepts of "East" and "West." Importantly, these concepts are often inextricably linked to other binaries such as .. religious/secular" and '·traditional/modem." The second portion of the theoretical model used for exploring Pamuk's literature is taken from Charles Taylor's essay Two Theories of Modernity, and his book Sources of the Self Alternative, or multiple modernities, in his view are inextricably linked to culture. Taylor also claims that the novel is a modem cultural form which relies on individual experiences in order to locate notions of the self. This forms an appropriate framework for exploring the way in which the concept of modernity influences Pamuk' s identity project in his novels. In a Turkish context, the ideology of equating '·West" with "Modernity" has had a profound effect on the way Turks view the process of modernization, which can be traced in the history of the novel in Turkey. The idea that the novel is a modern cultural form used to narrate identity is the common ground that Said and Taylor's theories share. Two of Pamuk's novels, namely The Black Book and The Museum of Innocence are analyzed in this dissertation in order to illustrate Pamuk's inclusion of religious/spiritual experiences as a central aspect in his search for identity. The ultimate conclusion is that the writing of novels for Pamuk is a kind of unique spiritual experience which is brought about by his use of Sufi motifs.